2016
DOI: 10.1186/s12866-016-0656-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption ionization time-of-flight mass spectrometry for rapid identification of mold and yeast cultures of Penicillium marneffei

Abstract: BackgroundPenicillium marneffei is the most important thermal dimorphic fungus causing systemic mycosis in HIV-infected and other immunocompromised patients in Southeast Asia. However, laboratory diagnosis of penicilliosis, which relies on microscopic morphology and mycelial-to-yeast conversion, is time-consuming and expertise-dependent, thus delaying diagnosis and treatment. Although matrix -assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) is useful for identification of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…In recent decades, penicilliosis has emerged in HIV-infected and other immunocompromised patients in various countries (3)(4)(5)(6). Since the disease carries a high mortality rate and is associated with relapse, finding ways to improve diagnosis and treatment is crucial (7,8). Moderate or severe penicilliosis is often treated with amphotericin B for 2 weeks, followed by maintenance with prolonged itraconazole to prevent relapse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, penicilliosis has emerged in HIV-infected and other immunocompromised patients in various countries (3)(4)(5)(6). Since the disease carries a high mortality rate and is associated with relapse, finding ways to improve diagnosis and treatment is crucial (7,8). Moderate or severe penicilliosis is often treated with amphotericin B for 2 weeks, followed by maintenance with prolonged itraconazole to prevent relapse.…”
mentioning
confidence: 99%
“…All T. marneffei strains were identified by conventional phenotypic tests and sequencing of three housekeeping genes (mannose phosphate isomerase [MPI], plasma membrane H ϩ ATPase [PM-ATPase], and pyruvate kinase [PK]) and by matrix-assisted laser desorption ionization-time of flight mass spectrometry as described previously (7). Yeast and mycelial cultures of T. marneffei were grown on Sabouraud dextrose agar (SDA) (Oxoid, Cambridge, United Kingdom) as described previously with modifications (14).…”
mentioning
confidence: 99%
“…Recently, matrix-assisted laser desorption ionization time-of-ight mass spectrometry (MALDI-TOF MS) was used to identify various clinically important fungi, including T. marneffei and related species [12]. If rapid and accurate identi cation is required, DNA sequencing or MALDI-TOF MS should be used.…”
Section: To the Editormentioning
confidence: 99%
“…Although these methods can provide accurate results, they are expensive, require specialized equipment or expertise, and are not commonly available in clinical laboratories. In the present review, findings from the 10 studies (23)(24)(25)(27)(28)(29)(30)(31)(32)(33) shown in Table 1 indicate that before MALDI-TOF MS testing, only one study identified isolates via conventional phenotypical analyses (33), whereas almost all the remaining studies also sequenced all their isolates, and in two studies, only molecular biology analyses of the isolates were undertaken (27,28). This supports the idea that the overall high level of accuracy of MALDI-TOF MS-based mold identification shown in these studies might not be overestimated.…”
Section: Mold Identification By Maldi-tof Ms: Is It Really a History mentioning
confidence: 99%
“…Nonetheless, demonstration of mycelium-to-yeast conversion, which is necessary for the definitive identification of the fungus, takes approximately 2 weeks, thereby delaying diagnosis and treatment. To our knowledge, a specific study focusing on the use of MALDI-TOF MS for the identification of T. marneffei appeared in the literature only very recently (28). In that study, spectra from mold and yeast cultures of 60 strains (59 clinical strains and 1 reference strain) of T. marneffei were analyzed with MALDI Biotyper 3.0 software against the Bruker database (BDAL version 4.0.0.1 and Filamentous Fungi Library 1.0), with or without the inclusion of additional spectra from T. marneffei strains selected from the set of test strains.…”
Section: Rhizopus-lichtheimia Species Previous Reports On the Maldi-mentioning
confidence: 99%